Analysis Of The Performance Of The Medan City Public Regional Market Enterprise In Market Retribution Management - Putra, Randy Tama; Nawawi, Zuhrinal M.; Harahap, Muhammad Ikhsan (UNIVERSITAS PAKUAN, 2017)
This research aims to determine the performance of the Regional Public Company of Medan City Market in managing the market retribution of Medan City. This research uses a qualitative research method. The research subject is PUD Pasar Kota Medan. The data collection techniques are document study and field research by conducting interviews. The data analysis technique uses the Balanced Scorecard analysis tool. The research results show that the performance of the Medan City Public Regional Market Company through the Balanced Scorecard approach is based on four perspectives, namely 1). The financial perspective shows good results, with the economic ratio falling within the economic criteria, the effectiveness ratio falling within the effective criteria, and the efficiency ratio needing improvement as the results indicate it is still less efficient. Based on the Islamic economic perspective, it aligns with the value of ownership. 2). The customer perspective shows that traders feel satisfied through validity and reliability tests. Based on the Islamic economic perspective, the customer perspective aligns with the values of justice in Islamic economics. 3). The internal business perspective indicates that Pud Pasar Kota Medan has provided good service and has innovated by implementing market retribution payments through Virtual Accounts. Based on the Islamic economic perspective, it aligns with the value of balance. 4). The growth and learning perspective shows that employee loyalty is very good and employee satisfaction indicates that employees feel satisfied based on validity and reliability tests. However, training for employees has not been well implemented. Based on the Islamic economic perspective, it aligns with the values of brotherhood and togetherness. Keywords: Company Performance, Market Retribution Management, Balanced Scorecard